KENDARI IMMIGRATION PODCAST (IKEPO) AS A MEANS OF INTRODUCING IMMIGRATION POLYTECHNICS TO THE PEOPLE OF SOUTHEAST SULAWESI - Wilda Ramadhani Mansur; Arief Febrianto (Jurnal Abdimas Imigrasi, 2021)
This socialization aims to introduce the Immigration Polytechnic to the people of Southeast Sulawesi through a Podcast held in collaboration with the Immigration Office Class I TPI Kendari under the name of the IKEPO program (Imigrasi Kendari Podcast). This podcast is broadcast live on Facebook, Instagram and YouTube and is part of a series of Immigration Polytechnic Latjapura 2021. Hopefully, the information provided by Immigration Polytechnic Students can increase public awareness about Immigration, especially Immigration Polytechnic and attract students in Southeast Sulawesi to continue their education at Immigration Polytechnic.